Situational Crime Prevention in Sexual Offenses Against Women: Offenders Tell Us What Works and What Doesn't. (July 2021) - Chiu, Yi-Ning; Leclerc, Benoit; Reynald, Danielle M.; Wortley, Richard
This study examined the perceived effectiveness of situational crime prevention (SCP) in sexual assault as rated by 140 offenders convicted for sex offenses against women in Australia. Participants were presented with three scenarios and asked to rate the perceived effectiveness of SCP techniques relating to guardianship, victim self-protective behavior, and crime prevention through environmental design (CPTED). Results indicate that the effectiveness of SCP methods was perceived to vary across different contexts. For offenses occurring in the private setting of an offender's home, victim self-protective behavior was seen as most effective, followed by guardianship and CPTED. In public settings, although the perceived effectiveness of victim self-protective behavior remained the same, guardianship and CPTED were rated as significantly more effective. Further variations were identified regarding specific strategies. Findings highlight the nuances of offender decision making in different situations and environments, and provide the first empirical comparisons of SCP perceptions among sex offenders.